(untitled) - Cahill, Spencer E. (New York, NY, 2010)
Provides an introduction to the sociological study of social psychology, interpersonal interaction, social construction, and the social shaping of human experience in our everyday lives
Keywords: Social psychology,Tâm lý học xã hội